Monte Carlo Simulation for Rattan Revenue: Production, Costs, and Demand Analysis - Igen Meyasha; Muhammad Erwanto (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
The rattan industry in Cirebon, Indonesia, is a significant part of the country's creative economy, but it faces several major challenges, including unstable production, fluctuating prices for raw materials, and uncertain demand, which make it difficult to predict income. The goal of this research is to create a quantitative model that can accurately forecast business income and help entrepreneurs make better financial decisions. The study employs the Monte Carlo simulation method to examine the impact of production levels, raw material costs, and demand on the revenue of rattan businesses. The simulation was run 10,000 times using probability distributions based on historical data. The results indicate that market demand and selling prices have the most significant positive impact on profits, while raw material costs have the most substantial negative effect on profits. The model illustrates the uncertainty of business conditions, with profit varying between IDR 19.5 billion and IDR 76.1 billion, averaging IDR 50.2 billion. The findings underscore the need to strike a balance between meeting growing demand and managing costs to achieve long-term profitability. This Monte Carlo-based model can be a valuable tool for rattan business owners and policymakers to support informed planning and mitigate risks.